Multi-Factor Crime in Malaysia, 1980 – 2013: Bounds Testing of Level Relationships and Granger Non-Causality Analysis / Dullah Mulok, Mori Kogid, Rozilee Asid, Jaratin Lily - Mulok, Dullah; Kogid, Mori; Asid, Rozilee; Lily, Jaratin (Faculty of Business and Management ; UiTM Press, 2018)
This study examines the relationship between criminal activities and the multi-macroeconomic factors of economic growth, unemployment, poverty, population and inflation in Malaysia from 1980 to 2013. The ARDL bounds testing of the level relationship was used to establish the long-run relation, and the Toda-Yamamoto Augmented VAR approach was used to test the short-run impact based on partial Granger non-causality analysis. Empirical results suggest that economic growth, inflation, poverty and population are significant factors affecting criminal activities in Malaysia with economic growth and poverty recording positive effects, whereas negative effects were recorded for inflation and population in the long-term. Further investigation using Granger non-causality analysis revealed that only population does Granger caused the criminal activities in the short-run. The findings provide useful information for policymakers to strengthen the existing crime-related policies in order to improve safety and security while maintaining economic sustainability in Malaysia.